2015
DOI: 10.1186/s13643-015-0037-z
|View full text |Cite
|
Sign up to set email alerts
|

The Epstein-Barr virus latent membrane protein-1 (LMP1) 30-bp deletion and XhoI-polymorphism in nasopharyngeal carcinoma: a meta-analysis of observational studies

Abstract: BackgroundEpstein-Barr virus (EBV) is considered to be closely associated with nasopharyngeal carcinoma (NPC), in which EBV-encoded latent membrane protein 1 (LMP1) was found to have an oncogenic role. However, the results published on the LMP1 polymorphism are inconsistent. In the present study, we performed a meta-analysis to determine the frequency of the associations and a more precise association between NPC and EBV LMP1 gene variants (30-bp deletion (del)/XhoI-loss).MethodsEligible articles met the inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 74 publications
0
31
1
1
Order By: Relevance
“…23,24 The del-LMP1 was first discovered in a NPC cell line derived from a patient in Southern China. 23 An association with this variant has been reported for several malignancies, including NPC, 17,25 but some studies have suggested that del-LMP1 is only a geographic polymorphism and is not restricted to EBV-associated malignancies. 26,27 In our study, we found del-LMP1 in eight of 43 EBV-positive cases, while the remainders were wt-LMP1.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 The del-LMP1 was first discovered in a NPC cell line derived from a patient in Southern China. 23 An association with this variant has been reported for several malignancies, including NPC, 17,25 but some studies have suggested that del-LMP1 is only a geographic polymorphism and is not restricted to EBV-associated malignancies. 26,27 In our study, we found del-LMP1 in eight of 43 EBV-positive cases, while the remainders were wt-LMP1.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of reports regarding the 30 bp-deletion of LMP1 have shown that this variation is widely spread worldwide [Hu et al, 1991;Sandvej et al, 1997;Correa et al, 2004;See et al, 2008;Tiwawech et al, 2008;Bobek et al, 2010;da Costa et al, 2015] -Table II. A recent meta-analysis, evaluated the association of this variation with NPC development and showed an association of del-LMP1 variant with NPC development described that the association is only observed in Asiatic populations while no association is observed for European and North African countries [da Costa et al, 2015]. Hence, del-LMP1 seems to be more prevalent in NPC patients than in healthy individuals and is expected to be more prevalent in NPC-endemic areas rather than non-endemic [Zhang et al, 2002;Plaza et al, 2003;Tiwawech et al, 2008;da Costa et al, 2015].…”
Section: Variations In Ebv Genomementioning
confidence: 99%
“…A recent meta-analysis, evaluated the association of this variation with NPC development and showed an association of del-LMP1 variant with NPC development described that the association is only observed in Asiatic populations while no association is observed for European and North African countries [da Costa et al, 2015]. Hence, del-LMP1 seems to be more prevalent in NPC patients than in healthy individuals and is expected to be more prevalent in NPC-endemic areas rather than non-endemic [Zhang et al, 2002;Plaza et al, 2003;Tiwawech et al, 2008;da Costa et al, 2015]. Similar results were found by other authors [Chang et al, 2009;Bobek et al, 2010;Banko et al, 2012;Gurtsevitch et al, 2013;Senyuta et al, 2014].…”
Section: Variations In Ebv Genomementioning
confidence: 99%
See 1 more Smart Citation
“…Эти мутации включали точечную мутацию, ведущую к потере сайта рестрикции XhoI в экзоне 1, и делецию 30 п.н. в карбокситерминальной области гена [43]. Было также показано, что обнаруженные мутации связаны с увеличением канцерогенности и снижением иммуноген-ности белка LMP1 [44,45].…”
Section: характеристика Lmp1unclassified